Konkurencja a współpraca : rola kapitału społecznego w rozwoju obszarów wiejskich - Sosenko, Barbara (Competition and Cooperation : the Role of Social Capital in the Development of Rural Areas, 2006)
The author puts forward the following thesis: cooperation as an element of social capital is, next to human capital, an extremely significant factor in the development of rural areas and a very important strategy of competition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 325-331